Effect of weight loss intervention for adults with severe intellectual disability by their mothers: A cluster randomized controlled trial - Mitsuyo Nonaka; Satoko Yanagisawa (PLoS ONE, 2025)
While adults with intellectual disabilities have a high prevalence of obesity, few weight loss interventions exist for them, and those that do exist target people with mild or moderate disabilities. To address obesity in adults with severe intellectual disabilities who are highly dependent, we developed the “Conflict-Free Weight Loss Program for Adults with Severe ID and Autism” to support their mothers and piloted the program, and the results showed that it was effective for weight loss. This study aimed to determine the feasibility of day center nurses and dieticians implementing the “Conflict-Free Weight Loss Program for Adults with Severe ID and Autism” and whether this would support effective weight loss in adults with severe intellectual disabilities, both with and without autism. A cluster randomized controlled trial per day center was registered at UMIN Clinical Trials Registry (UMIM-CTR ID;UMIN000047478) and was conducted with 31 adults with severe intellectual disabilities in Aichi, Japan. The seven-month trial consisted of a four-month intervention and a three-month follow-up; 15 adults in the intervention group and 13 in the control group completed the follow-up. Primary outcomes included the adults’ weight and waist circumference, and differences between groups were analyzed using the Friedman tests. The secondary outcomes were mothers’ implementation, adults’ scores for inflexible adherence, and daily intake of target food. The intervention group showed significantly reduced weight (median; baseline 1, post-intervention 0.975, follow-up 0.983, p <  0.001), and slightly reduced waist circumference (median; baseline 1, post-intervention 0.975, follow-up 0.975, p =  0.226); however, the control group showed no change. Adults’ resistance was minimal, maternal implementations were high, and daily food intake decreased. Our findings indicate that our program was feasible for day center nurses and dietitians to implement and has the potential to reduce the weight of adults with severe intellectual disabilities.